Role of Nebulized Heparin in Patients with Acute Respiratory Distress Syndrome on Mechanical Ventilation (Bangladesh Critical Care Journal, 2025)
Background: Acute respiratory distress syndrome (ARDS) is a grave condition, where pulmonary coagulopathy; an important contributor to hypoxia, which ultimately cause multiorgan dysfunction and leads to death. Heparin is an anticoagulant, that has the potential to modify that coagulopathy. So, in addition of current guideline, nebulized heparin may be beneficial for treating patients with ARDS on mechanical ventilation. Methods: This is a randomized controlled trial. A total of 74 sample sizes had been estimated by using statistical formulas. In this study, patients were diagnosed as ARDS according to Berlin definition by the ICU physicians. Study patients were allocated systemically in two groups. The randomized procedure involved first assigning the initial ARDS patient by a coin flip, subsequent patients were then assigned alternately to the intervention or control group on their order of diagnosis (odd-even sequence). One group received nebulized heparin in addition to protocolized treatment for ARDS and another group received only protocolized treatment for ARDS. Patients received the intervention, got nebulized heparin 5000u mixed with 2 ml normal saline/BD for a week along with protocolized treatment for ARDS and patients of control group or standard of care group, got only protocolized treatment but no heparin nebulization. Result: The mean tidal volume was significantly different on the third day and fifth day (p < 0.05), no significant difference regarding the mean respiratory index (PaO2/FiO2) on the first day, while it increased significantly in the intervention group on the third, fifth and seventh day (p < 0.05). There was no significant difference of platelet count and APTT in two groups (p > 0.05). Conclusion: The administration of heparin nebulization can enhance oxygenation, evidenced by improving PaO2/FiO2 in ARDS patients on mechanical ventilation.Bangladesh Crit Care J September 2025; 13 (2): 100-103